Clinical translation of immunoliposomes for cancer therapy: recent perspectives. (2nd September 2018) - Wang, Di; Sun, Yating; Liu, Yange; Meng, Fanchao; Lee, Robert J.
ABSTRACT: Introduction : Liposomes have been extensively investigated as drug delivery vehicles. Immunoliposomes (ILs) are antibody-conjugated liposomes designed to selectively target antigen-expressing cells. ILs can be used to deliver drugs to tumor cells for improving efficacy and reducing toxicity. In addition, ILs can be used in immunoassays, immunotherapy, and imaging. Although there has been extensive coverage on ILs in the literature, only a limited number of clinical trials have been reported and no IL drug has been approved by the FDA. Areas covered : Factors to consider in developing ILs are discussed, including the choice of antibody or antibody fragment, the formulation of liposomes, and the conjugation chemistry. In addition, challenges and opportunities in clinical development of ILs are discussed. The purpose of this review is to provide an overview on the state of the art of ILs and to discuss potential future developments. Expert opinion : IL research has had a lengthy history and numerous preclinical studies have yielded encouraging results. However, there are a number of obstacles to clinical translation of ILs. Given the unique capabilities of ILs, its potential for clinical application is underexplored. There is great potential for expanded role for ILs in the clinic and further efforts to this end are warranted. Abbreviations : Ab : antibody; ADCs: antibody-drug conjugates; API: active pharmaceutical ingredient; ADCC: antibody-dependent cellular cytotoxicity; CR: complete remission; cGMP: current good manufacturing practice; DSPE: distearoyl phosphatidylethanolamine; EGF: epidermal growth factor; EGFR: epidermal growth factor receptor; EPR: enhanced permeability and retention; Fc: fragment crystalline; Tf: transferrin; HACA: human-anti-chimeric antibody; HAHA: human-anti-human antibody; HAMA: human-anti-mouse antibody; HER2: human epidermal growth factor 2; IL: immunoliposome; LNPs: lipid nanoparticles; MRI: magnetic resonance imaging; MTD: maximum tolerated dose; PEG: polyethylene glycol; PET: positron emission tomography; PR: partial response; PSMA: prostate-specific membrane antigen; scFv: single-chain variable fragment; SPECT: single photon emission computed tomography; TTR: transthyretin